Linked pacing after heterotopic heart transplantation with concurrent left ventricular reduction of the native heart. - Beyer, E (1998)
A 30-year-old man with dilated cardiomyopathy underwent heterotopic heart transplantation, concurrently with surgical reduction of the native left ventricle, a mitral valvuloplasty, and an apical thrombectomy. Postoperatively, the patient had hemodynamic instability that was refractory to conventional medical therapy. Temporary sequential pacing of the 2 hearts was used to induce timed counterpulsation, which resulted in marked hemodynamic improvement. To the best of our knowledge, this case involves the 1st report in the English-language literature of clinical usage of paced, linked counter-pulsation to treat acute hemodynamic compromise early after heterotopic heart transplantation.